The beauty of mathematics in computer science - Wu, Jun 1967- (Routledge, an imprint of the Taylor & Francis Group, 2019)
"A series of essays introducing the applications of machine learning and statistics in natural language processing, speech recognition and web search for non-technical readers."--Provided by publisher